A simple current control strategy for a four-leg indirect matrix converter - Garcia, Cristian; Rivera, Marco; Lopez, Miguel; Rodriguez, Jose; Pena, Ruben; Wheeler, Patrick; Espinoza, Jose (Institute of Electrical and Electronics Engineers, 2014)
In this paper the experimental validation of a predictive current control strategy for a four-leg indirect matrix converter is presented. The four-leg indirect matrix converter can supply energy to an unbalanced three-phase load whilst providing a path for the zero sequence load. The predictive current control technique is based on the optimal selection among the valid switching states of the converter by evaluating a cost function, resulting in a simple approach without the necessity for modulators. Furthermore, zero dc-link current commutation is achieved by synchronizing the state changes in the input stage with the application of a zero voltage space vector in the inverter stage. Simulation results are presented and the strategy is experimentally validated using a laboratory prototype.